2020
DOI: 10.3390/ani10122200
|View full text |Cite
|
Sign up to set email alerts
|

Daily Activity Patterns and Co-Occurrence of Duikers Revealed by an Intensive Camera Trap Survey across Central African Rainforests

Abstract: The duiker community in Central African rainforests includes a diversity of species that can coexist in the same area. The study of their activity patterns is needed to better understand habitat use or association between the species. Using camera traps, we studied the temporal activity patterns, and quantified for the first time the temporal overlap and spatial co-occurrence between species. Our results show that: (i) Two species are strongly diurnal: Cephalophus leucogaster, and Philantomba congica, (ii) two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 57 publications
0
8
0
1
Order By: Relevance
“…Camera traps have grown in popularity among researchers investigating activity patterns with adequate behavioral information captured by remote cameras [33]. A number of recent studies have demonstrated the utility of this technique to quantify activity patterns of target species and their interspecific overlaps [34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…Camera traps have grown in popularity among researchers investigating activity patterns with adequate behavioral information captured by remote cameras [33]. A number of recent studies have demonstrated the utility of this technique to quantify activity patterns of target species and their interspecific overlaps [34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…The use of camera-traps has provided important ecological information concerning the spatiotemporal behavior of wild species, including species of conservation interest [ 4 ], rare/elusive species [ 5 , 6 , 7 ], as well as problematic species requiring management action such as alien species [ 8 , 9 ]. It has been shown that 30–100 independent camera-trap records per species for each season or year may be sufficient to estimate activity rhythms of wildlife, with results comparable to those obtained from GPS or radio-tracked animals [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…P. monticola ; Mockrin et al, 2011) and modifications of diel activity patterns. Philantomba monticola , which usually has bimodal daily activity (Dubost, 1980; Bowland & Perrin, 1995; Houngbégnon et al, 2020), exhibited only one activity peak in our study area. This could be interpreted as the species avoiding the hours during which hunters are active, but our data do not allow us to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 51%